Proposal of reference landscape to assess landscape indexes performance. Tagua Tagua park case, Chile - Cruz Johnson, Pablo; Gorospe Ballesteros, Juan Manuel (Instituto de Ecología, A.C., 2019)
The objective of this work was the proposal of a method that allows quantitative measurement of effects of restoration activities at landscape scale, comparing an initial conservancy condition, with another one ideal, called reference landscape created by projecting the hoped for changes by restoring. Once the reference landscape was defined, an assessment of landscape indexes that allowed measure conservation gain by restoration was proposed. In order to achieve this goal, the work was developed in a basin with high conservation level. The landscape indexes used were: edge effects, diversity landscape index, form index and, spatial continuity index, applying each of them to the initial condition and to the reference landscape. For the studied case, the reference landscape was simple an easily defined, due to the vast amount of information available for the forest in the area. In the stage of landscape index evaluation, those ones with the best performance to measure conservation gain were edge effect and spatial continuity. Form index, instead, created confusing values between initial condition and reference landscape. So too, diversity index forced a complex analysis, mainly because restoration modified the class number between initial conditions and reference landscape.